Alkali barium glasses for hermetic compression seals: Compositional effect, processing, and sealing performance. Issue 17 (1st December 2019) - Guo, Hongwei; Dang, Mengyang; Liu, Lei; Tong, Qiang; Zhao, Congcong; Carlson, Krista; Gong, Yuxuan; Hoffman, John W.
Abstract: Electrical connectors are being used in a variety of areas including civil use, defense technology, aerospace technology, and etc. The application of electrical connectors at extreme conditions (e.g. under extreme strain, pressure, and temperature) calls for superior thermal performance, chemical durability, and electrical properties (e.g. dielectric constant) of sealing glasses. In this study, the mixed alkali effect (between Na and K) of modified alkali barium aluminoborosilicate glasses was studied as a function of thermal properties, electrical resistivity, and chemical durability. Glasses used in this study were modified upon a commercially available compression sealing glass, Elan 13 glass, which was a lead-free substitute for Corning 9013 glass. It was found that the mixing of alkali (Na and K) and alkaline earth (Ca and Mg) can be used to optimize the physico-chemical properties of the resultant glasses, with performance better than or equivalent to the Elan 13 glass. In addition, optimized properties can be achieved at the following compositional space: 59.0 to 65.0 wt% of SiO2, 3.0 to 4.5 wt% of B2 O3, 3.0 to 4.5 wt% of Al2 O3, 11.0 to 18.0 wt% of R2 O, 11.0 to 13.0 wt% of BaO, 1.2 to 1.4 wt% of CaO, and 0.3 to 0.6 wt% of MgO. The resultant glasses can sealed at 950 o C for 30 min with an adhesion strength of 98 MPa, a leaking rate of 5×10 -10 Pa·m 3 /s, and pass ratings on resistance and dielectric breakdown strength.